The science fiction mythmakers : religion, science and philosophy in Wells, Clarke, Dick and Herbert - Simkins, Jennifer, 1986- (McFarland & Company, Inc., Publishers, 2016)
"This book considers the significance of this confluence through an examination of myths in the writings of H. G. Wells, Arthur C. Clarke, Philip K. Dick and Frank Herbert. Presenting fresh insights into their works, the author brings to light the tendency of science fiction narratives to reaffirm spiritual myths"--Resumé vydavatele
Keywords: vědecko-fantastická literatura; americká literatura; anglická literatura; literárněvědné rozbory; mýty; literatura a náboženství; science fiction; American literature; English literature; literary criticism and history; myths; literature and religion; studie; studies